Marketing Strategies in Maintaining a Business According to an Islamic Economic Perspective: Case Study of Teh Desa Outlet in Pekalongan - Karismatun Khasanah; Muhammad Shulthoni; Hendri Hermawan Adinugraha (Syamilah Publishing, 2024)
This research aims to find out more about the marketing strategies used in maintaining business at the Teh Desa outlet, whether it has met the maximum standars or not. This research usesfield reserach with a descriptive qualitative approach. Then for the location of this research was conducted in Pekalongan, Central Java. The results of this study found that the 4P marketing buaran strategy at Es Teh Desa has a positive impact on sales. In addition, the sharia marketing strategy applied to Teh Desa in Pekalongan is in accordance with the principles of Islamic law, namely with pricing and promotion strategies that are in accordance with Islamic law by always being guided by the rules, limits in doing business, avoiding fraund and inaccurate doses. This is evidenced that the Teh Desa business hass implemented sharia marketing practices which consist of divinity (rubbaniyah), ethical (akhlaqiyah). realistic (waqi'iyah) and humanities (al-insaniyah) and all of which are the foundation of the marketing strategy carried out by the owner of the Teh Desa outlet in Pekalonga.